العلاج الجراحي لهبوط القدم التالي لأذية العصب الشظوي المشترك بتقنية نقل الأوتار( النتائج الوظيفية) - حلوم, غياث (Latakia University Journal -Medical Sciences Series, 2017)
بلغ عدد المرضى  مريضاً, تراوح عدد الإناث  مريضة بنسبة مئوية  %, عدد الذكور  مريضاً بنسبة  % . العمر الوسطي لفترة حدوث الأذية كان العقد الثالث. شملت عينة المرضى الأذيات التامة للعصب الشظوي المشترك المعزولة التالية للرض فقط.اعتمدنا في تشخيص هذه الإصابات بشكل أساسي على الدراسة السريرية التي اتبعت بإجراء تخطيط كهربية الأعصاب والعضلات والذي اظهر فقدان تام لمقدرة العصب على الاستجابة للتنبيه الكهربائي. مانأمله من معالجة هذه الحالات هو الحفاظ على وظيفة مقبولة نسبياً وليس العودة التامة لها حيث يجمع المؤلفون أنه لايمكن أن تعود الوظيفة %. حصلنا على نتائج جيدة بعد مرور سنة على العمل الجراحي من حيث المقوية العضلية لعضلات الساق % بالإضافة إلى تحسن جيد في مجال حركة مفصل عنق القدم  %.واظب كل مرضى على المعالجة الفيزيائية في مركز متخصص بالعلاج الفيزيائي بعد نزع الجبس. أظهرت الدراسة أن التعاون التام والمنتظم بين طبيب الجراحة المعالج وطبيب المعالجة الفيزيائية له دور كبير في الحصول على نتائج الجيدة. The number of patients reached 15 patients, the number of females ranged was 1 patient percentage 6,6%, The number of males 14 ranges by 93.4% . Mean age of the occurrence of the injury was at the third decade.The patients of the Study had isolated common peroneal nerve injuries after Trauma.We have basted in the diagnosis of these injuries mainly on the clinical study, which followed by EMG, it showed loss of the ability of the nerve to respond to alert the electric stimulation. we hope with these situations is to maintain a relatively acceptable function, not a full return of it, Authors said that the function cannot return 100%. We have good results one year after the surgery in terms of muscle tone of the leg 67%, In addition to a good improvement in the movement of ankle joint 60%. All patients followed physical therapy in specialized Center in physical therapy after removing the plaster.The study showed that a full and regular cooperation between the surgeon therapist and adoctor of physical therapy has a big role in getting agood results.